Implementation of the Cultural Values of the “Taneak Jang” ‎Customary Tradition in Strengthening Literacy and ‎Indonesian Language Learning in Junior High Schools - Agung Nugroho; ‎ Cekman; Juwati; Dian Ramadan; Satinem (JPI: Jurnal Pustaka Indonesia, 2026)
This study aimed to describe the implementation of the Taneak Jang customary tradition, examine the role of customary leaders in its preservation, identify factors supporting its continuity, and explore its relevance to cultural literacy and Indonesian language learning in junior high schools. A descriptive qualitative design with a cultural ethnographic approach was conducted in Pasenan Village, STL Ulu Terawas District, Musi Rawas Regency. Data were obtained from customary leaders, bayan, community leaders, and residents involved in the tradition through in-depth interviews, direct observation, and documentation, then analysed through data reduction, data display, and conclusion drawing. The findings showed that Taneak Jang is implemented through the preparation of ritual equipment, the bridal procession, melangir, mandi kasai, simburan, and closing prayers. Customary leaders functioned as ritual leaders, guardians of procedural authenticity, providers of moral and spiritual guidance, and transmitters of cultural knowledge. The tradition was sustained by community attachment to ancestral customs, family participation, customary leadership, village-government support, and intergenerational transmission. Its pantun, prayers, advice, narratives, and symbolic practices were identified as potential materials for descriptive, narrative, expository, and procedural texts, cultural literacy, and character education. These findings indicate that living oral traditions can connect language learning with students’ sociocultural environment and support local-identity preservation, consistent with contextual and culture-based learning perspectives. However, the study was limited to one village and did not test classroom implementation; future research should develop and evaluate Taneak Jang-based teaching materials across different schools and learner groups.